Mississippi after Katrina disaster recovery and reconstruction on the Gulf Coast - Trivedi, Jennifer, 1982- (Lexington Books, 2020)
"In Mississippi After Katrina, Jennifer Trivedi takes an holistic anthropological lens to the city of Biloxi, Mississippi, and illustrates how Hurricane Katrina revealed the cultural, political, and economic issues that shaped the community's history, the storm's impact, and Biloxi's long-term recovery from Katrina"--